Analisis Kesesuaian Penggunaan Lahan pada Sempadan Danau Batur, Provinsi Bali - Ni Nyoman Samitri Putri; I Dewa Gede Agung Diasana Putra; I Gusti Ngurah Anom Rajendra (P4W LPPM IPB, 2023)
Batur lake is one of the lakes designated as world cultural heritage considering the importance and role of Batur lake and its environment culturally, economically and ecologically. Various activities from various sectors grow around Batur lake which could change the land use and have a negative impact on the panorama of the lake. Therefore, this study aims to determine the boundary of Batur lake viewed from the development of water level rise to describe the suitability of land use in the Batur lake border, as well as to develop strategies for land use mismatches that occur. Data were collected through primary and secondary surveys. Statistical-descriptive analysis techniques in the form of data processing digitization with geospatial information systems and land use evaluations were carried out based on land suitability analysis, followed by comparing existing land use with the direction of activities in related regulations. Results shows the direction of land suitability on Batur lake border, are the buffer area and the development of annual plants. The land cover ratio of each direction is still in accordance with the maximum limit. In addition, there are land uses that are not suitable, such as plantation agriculture and non-annual crops, as well as trade and services, in the form of tourism accommodation.